Decreased in vitro Mitochondrial Function is Associated with Enhanced Brain Metabolism, Blood Flow, and Memory in Surfl-Deficient Mice. Issue 10 (October 2013) - Lin, Ai-Ling; Pulliam, Daniel A; Deepa, Sathyaseelan S; Halloran, Jonathan J; Hussong, Stacy A; Burbank, Raquel R; Bresnen, Andrew; Liu, Yuhong; Podlutskaya, Natalia; Soundararajan, Anuradha; Muir, Eric; Duong, Timothy Q; et al.
Recent studies have challenged the prevailing view that reduced mitochondrial function and increased oxidative stress are correlated with reduced longevity. Mice carrying a homozygous knockout (KO) of the Surf1 gene showed a significant decrease in mitochondrial electron transport chain Complex IV activity, yet displayed increased lifespan and reduced brain damage after excitotoxic insults. In the present study, we examined brain metabolism, brain hemodynamics, and memory of Surf1 KO mice using in vitro measures of mitochondrial function, in vivo neuroimaging, and behavioral testing. We show that decreased respiration and increased generation of hydrogen peroxide in isolated Surf1 KO brain mitochondria are associated with increased brain glucose metabolism, cerebral blood flow, and lactate levels, and with enhanced memory in Surf1 KO mice. These metabolic and functional changes in Surf1 KO brains were accompanied by higher levels of hypoxia-inducible factor 1 alpha, and by increases in the activated form of cyclic AMP response element-binding factor, which is integral to memory formation. These findings suggest that Surf1 deficiency-induced metabolic alterations may have positive effects on brain function. Exploring the relationship between mitochondrial activity, oxidative stress, and brain function will enhance our understanding of cognitive aging and of age-related neurologic disorders.